PEMBUATAN SISTEM INFORMASI BERBASIS WEB DI SD ISLAM TERPADU AL-KHAIRAT MENGGUNAKAN PHP DAN MYSQL - Harno Priyanto; Erfanti Fatkhiyah (Jurnal SCRIPT, 2016)
Website is a promotional and information media at this time. Because the internet service are familiar to the people. SD IT Al-Khairaat is a school that does not have a website but eager to have it in order to easier in providing information and promotion to the people. So there needs to be an development of SD IT Al-Khairaat’s website which can be accessed online and can be an effective information and promotional media. With the purpose of facilitating the people to access and find out information from SD IT Al-Khairaat. This research building web-based information system and integrated with PHP in order to website’s page can display content dinamically. Data content displayed is taken from the MySQL database which can be updated by admin. In making of this information system has several stages,namely data collection, designing the look of the website according to the data, designing database according to the data, implementation of the system design and testing the system. This research resulted SD IT Al-Khairaat’s Web Based Information System that can be used by the school as an effective information and promotional media and can be accessed online by the public.